Peran Dewan Pengawas Syariah dalam Meningkatkan Kepercayaan Publik terhadap Lembaga Keuangan Syariah - Adinda Umul Fadzila; Anton Bagus Santoso; Muhammad Miftakhu Surur; Reniy Widiastuti; Laily Nurul Hidayah; Muhammad Taufiq Abadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
The Sharia Supervisory Board (DPS) is a board formed to oversee the running of the company so that it can run in accordance with sharia principles. Supervision of the company is in line with the rampant moral hazard in the form of fraud, cheating and money lending that is carried out so that it results in a loss of public trust in several financial institutions in Indonesia. Therefore, the role of DPS is needed as the foundation of sharia financial institutions to keep the company in accordance with sharia so that public trust can ultimately be fulfilled. The method used in this research is qualitative with a description-analytical approach and the type of research is library research, namely research whose object of study uses library data in the form of books as a source of data. Public trust is an important factor in the development of financial institutions in Indonesia. In its development, DPS has not been able to optimize its role as a supervisor of LKS operations or as a driver of economic development in accordance with sharia principles. This is due to the challenges that must be faced, namely the limitations of competent scholars and the lack of optimization of supervision. To face this challenge, efforts are needed to optimize the role of DPS as follows: First, socialization and training should be held both among financial institutions and to the public. Second, DPS can determine and determine members who will become candidates for the Sharia Supervisory Board to carry out their duties as DPS and not underestimate their position.